Photo-Polymerization in Chiral Dopant Liquid Crystal Cells via Holographic Exposure to Fabricate Polarization-Independent Phase Modulator with Fast Optical Response - Chien, Chun-Yu (Polymers (Basel), 2018)
Small liquid crystal domains with random director distributions were obtained to show novel optical isotropy using a holographic exposure processes to treat chiral dopant liquid crystal cells in the isotropic phase (i.e., polymer-stabilized isotropic liquid crystal cells). The cells used to fabricate phase modulators showed unique performances, including low light scattering, polarization-independence, and fast optical response. Furthermore, an extra fluoro-surfactant dopant in cells showed that the phase modulators retained their performance but with considerable reduction of operating voltages, from 180 V(rms) to 100 V(rms).